Nylon resin and preparation process thereof
Through cold crystallization treatment and optimization of the molecular chain structure of nylon resin, the problem of insufficient dyeing rate and coloring effect of nylon 12-element long-chain nylon during dyeing is solved, and the excellent dyeing performance and high color fastness of nylon fibers are achieved, reducing processing costs and risk of wire breakage.
Patent Information
- Application Number
- CN202510003064.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-02
- Publication Date
- 2025-04-11
AI Technical Summary
The dyeing rate and coloring effect of nylon 12 are low during dyeing, which cannot meet the requirements of clothing fabrics for color brightness. At the same time, screw modification processing is prone to introduce impurities, increasing processing costs and risk of wire breakage.
The DSC curve of long-chain nylon resin was tested by using a fast scanning calorimeter, and dyed at a lower temperature by cold crystallization treatment, and then crystallized at a high temperature to fix the color, optimize the molecular chain structure of nylon resin and improve the dyeing performance.
It realizes excellent dyeing performance of nylon fiber, improves dyeing rate and dyeing rate, enhances the color fixation effect and color fastness of the fiber, and reduces processing costs and risk of wire breaking.
Smart Images

Figure BDA0005226000990000061 
Figure BDA0005226000990000071
Abstract
Description
Technical Field
[0001] The invention relates to the field of nylon, and in particular to a nylon resin with excellent dyeing performance and a preparation process thereof. Background Art
[0002] The dyeing performance of the fiber depends on the dispersibility of the dye and the affinity between the fiber and the dye. Generally, acid dyes contain sodium sulfonate groups, which can combine with the amino group (-NH) of nylon fiber through ionic bonds or electrostatic interactions, thereby providing better dyeing effects. From the perspective of dyeing uniformity, acid dyes are the first choice for dyeing nylon fibers, so acid dyes are the most popular applications used in related industries.
[0003] Compared with conventional nylons such as nylon 6 and nylon 66, long-chain nylons such as nylon 12 have the characteristics of low density, good low-temperature toughness, low water absorption, and excellent wear resistance. When long-chain nylons such as nylon 12 are made into fibers for textile fabrics, the fabrics have the performance advantages of lightness, high strength, wear resistance, and high cold resistance. However, the amide bond density of long-chain nylons such as nylon 12 is lower than that of nylon 6 and nylon 66, which makes its dyeing rate and coloring effect lower during dyeing, and cannot meet the requirements of clothing fabrics for color brightness.
[0004] EP2292680B1 uses a chemical substance containing an amino group, a hydroxyl group or an epoxy group as a compatibilizer, adds the compatibilizer to polyamide by screw modification, and then uses an acid dye for dyeing, thereby improving the dyeing effect of the polyamide fiber. However, the screw modification process easily causes the polymer to decompose and yellow during the processing, and is easy to introduce impurities, making the modified resin prone to broken fibers during spinning, especially during ultrafine fiber spinning. In addition, the processing cost will also increase. Summary of the invention
[0005] In order to solve the above problems existing in the prior art, the present invention provides a nylon resin and a preparation process thereof. The obtained nylon fiber is dyed at a relatively low temperature and then cold crystallized and fixed at a higher temperature, thereby obtaining a nylon fiber with excellent dyeing performance.
[0006] In order to achieve the above object, the present invention provides the following technical solutions:
[0007] In a first aspect of the present invention, a nylon resin is provided, wherein the nylon resin has the following characteristics:
[0008] (a) The DSC curve of the long-chain nylon resin was tested using a rapid scanning calorimeter. The temperature was first increased to 220°C at a rate of 10 K / min, then decreased to 20°C at a rate of 30 K / min, and then increased to 220°C at a rate of 10 K / min. During the second temperature increase, a cold crystallization exothermic peak was generated. The exothermic peak temperature was measured to be 75-95°C (preferably 90-95°C), and the crystallization heat release was 55-75 J / g (preferably 70-75 J / g).
[0009] Cold crystallization is understood to mean crystallization that occurs after heating to above the softening temperature or glass transition temperature. The cold crystallization temperature is the temperature at which the first exothermic maximum of free energy occurs. Exothermic means the release of energy.
[0010] (b) The relative viscosity measured in m-cresol as solvent at 25°C and a concentration of 0.5 g / dL is 2.0-2.2.
[0011] According to the nylon resin provided by the present invention, in some embodiments, the nylon resin also has the following characteristics:
[0012] (c) The molecular weight distribution of the nylon resin was measured by gel permeation chromatography in hexafluoroisopropanol as a solvent and was found to be 2.85-3.15.
[0013] In a second aspect of the present invention, a preparation process of the nylon resin is provided. The nylon resin is obtained by copolymerizing diamine and dicarboxylic acid monomers.
[0014] The diamine is preferably an aliphatic diamine, such as an aliphatic straight-chain diamine or an alicyclic diamine, more preferably one or more of 4,4-diaminodicyclohexylmethane (PACM), 3,3-dimethyl-4,4-diaminodicyclohexylmethane (MACM), 4,4-isopropyldicyclohexylamine (PACP), 2,4-methylcyclohexanediamine (HTDA), 1,4-cyclohexanediamine, 1,3-cyclohexanedimethylamine, isophoronediamine, and 1,2-cyclohexanediamine.
[0015] The dicarboxylic acid is preferably one or more of isophthalic acid, terephthalic acid, undecanedioic acid, dodecanedioic acid, tridecanedioic acid, and tetradecanedioic acid.
[0016] In some embodiments, the nylon resin preparation process further includes lactam and / or water and / or a capping agent and / or a catalyst.
[0017] The lactam is selected from laurolactam and / or caprolactam.
[0018] The end-capping agent is selected from one or more of oxalic acid, adipic acid, sebacic acid, terephthalic acid, and isophthalic acid.
[0019] The catalyst is selected from one or more of dibutyl phosphate, sodium hypophosphite, hypophosphorous acid, trimethyl phosphate or triphenyl phosphite.
[0020] In some embodiments, the preparation process of the nylon resin comprises the following steps:
[0021] The diamine, dicarboxylic acid, lactam, water, an optional catalyst and a capping agent are mixed, and the pressure, temperature and time of the reaction process are controlled to carry out a polymerization reaction to obtain a nylon resin.
[0022] Specifically, the reaction pressure is -60KPa to 30KPa, the reaction temperature is 240-300°C, and the reaction time is 5h-15h.
[0023] In a specific embodiment, the preparation process of the nylon resin comprises the following steps:
[0024] (1) mixing lactam, diamine, dicarboxylic acid, water and end-capping agent and reacting them, and then releasing the pressure of the reaction system to normal pressure;
[0025] (2) The reaction system is kept at a pressure of 10 to 30 kPaG for 1 to 3 hours;
[0026] (3) The reaction system is evacuated to a pressure of -70 to -90 kPaG for 0.5 to 1.5 h;
[0027] (4) The reaction system is adjusted to normal pressure, and the material is discharged, water-cooled, and pelletized to obtain nylon resin.
[0028] In the present invention, relative to the total mass of the nylon resin, the total mass fraction of the diamine and the dicarboxylic acid is 15-25%, and the molar ratio of the diamine to the dicarboxylic acid is (0.8-1.2): (0.8-1.2).
[0029] In the present invention, compared with the total mass of the nylon resin, the mass fraction of the end-capping agent is 0.1-0.5%, preferably 0.2-0.3%.
[0030] In the present invention, water is used as an initiator for the lactam ring-opening reaction and a solvent for the copolymerized nylon salt, and the mass ratio of water to nylon resin is 1:(5-30), preferably 1:(15-20).
[0031] In the present invention, compared with the total mass of the nylon resin, the mass fraction of the lactam is 74.8-84.8%;
[0032] In the present invention, the reaction temperature in step (1) is 240-280° C., and the reaction residence time is 3-5 h.
[0033] In the present invention, the reaction temperature in steps (2) to (4) is 240-260°C.
[0034] The total mass of the nylon resin of the present invention is the sum of the masses of the lactam, the diamine, the dicarboxylic acid and the end-capping agent.
[0035] The present invention optimizes the molecular segment structure of long-chain nylon by controlling reaction pressure and time through staged polycondensation, thereby reducing the crystallinity of the resin during initial processing and molding, so that the cold crystallization temperature and heat release of the nylon resin during the second heating process meet the range. The nylon resin obtained at this time has excellent dyeing performance when dyeing.
[0036] In a third aspect of the present invention, there is provided use of the nylon resin for dyeing textile fibers.
[0037] In some embodiments, after the obtained nylon resin is made into 70D / 24F bundles, the bundles are immersed in an acid dye solution for dyeing, and are kept warm at 60-75°C for 0.5-1h, and then heated to 80-90°C at a rate of 3-5°C / min and kept warm for 30-45min.
[0038] The nylon resin provided by the invention is used for fabric fibers, and the dyeing rate is 85-99%, preferably 97-99%, and the rubbing color fastness is above level 3, preferably above level 4.
[0039] Compared with the prior art, the present invention has the following beneficial effects:
[0040] (1) The nylon resin with specific properties provided in the present invention optimizes the polycondensation process and divides the post-polycondensation process into two stages, respectively reacting under positive (steam) pressure and high vacuum, thereby optimizing the molecular chain structure of the nylon resin, reducing the crystallinity of the resin during initial processing and molding, and controlling the temperature required for cold crystallization heat treatment within a certain range. The nylon resin thus obtained has excellent dyeing properties when used for textile fibers.
[0041] (1) The molecular chain regularity of the nylon resin of the present invention is poor, so that it is not completely crystallized during the initial spinning process, thereby reducing the crystallinity of the obtained nylon fiber, which is conducive to the dyeing of the nylon fiber at a lower temperature. The dye is more easily diffused from the surface of the nylon fiber to the inside of the fiber, thereby improving the dyeing rate and dye uptake of the fiber; after the dyed fiber is subsequently heated to a higher temperature and kept for a period of time, the nylon fiber re-crystallizes and the crystallinity is increased, thereby improving the color fixation effect of the fiber, so that the color fastness of the fiber is improved. DETAILED DESCRIPTION
[0042] In order to better understand the technical solution of the present invention, the content of the present invention is further described below in conjunction with the embodiments, but the content of the present invention is not limited to the following embodiments.
[0043] The present invention is further described below in conjunction with specific embodiments, but the present invention is not limited to the following embodiments.
[0044] Lauryl lactam, 4,4-diaminodicyclohexylmethane, 3,3-dimethyl-4,4-diaminodicyclohexylmethane, 1,4-cyclohexanediamine, dodecanedioic acid, isophthalic acid, adipic acid and acid red dye 88 are all commercially available raw materials.
[0045] The relative viscosity is measured according to ISO 1628-1:1998 at 25°C in a 0.5 g / dL m-cresol solution using a Hangzhou Zhuoxiang IV2000 Ubbelohde viscometer.
[0046] Molecular weight distribution (D): The test was conducted using Shimadzu high performance liquid chromatography LC-20A with hexafluoroisopropanol as solvent to measure the number average molecular weight Mn and the weight average molecular weight Mw, D = Mw / Mn.
[0047] DSC curve: Using Mettler DSC 3 (differential scanning calorimeter) to test, the nylon resin was first heated to 220°C at a rate of 10K / min, then quickly cooled to 20°C at a rate of 30K / min, and then heated to 220°C at a rate of 10K / min. The cold crystallization exothermic peak temperature and heat released during the second heating process were measured.
[0048] The dye uptake test was carried out using the residual liquid method on a 723 spectrophotometer and the dye uptake was calculated;
[0049] The color fastness to rubbing is tested in accordance with GB / T 3920-1997.
[0050] Comparative Example 1
[0051] In a 1m 3 In a stirring container, 239.4 kg of laurolactam, 20 kg of water, 600 kg of end-capping agent adipic acid, 28.638 kg of 4,4-diaminodicyclohexylmethane, and 31.362 kg of dodecanedioic acid were added, the temperature was raised to 260 ° C and kept for 3 hours, the system was depressurized to normal pressure, and the vacuum degree was maintained at -50 KPaG at 250 ° C and kept for 3 hours. After the system returned to normal pressure, the material was discharged at 250 ° C and water-cooled and pelletized to obtain nylon resin.
[0052] Comparative Example 2
[0053] In a 1m 3In a stirring container, 239.4Kg of lauryl lactam, 20Kg of water, 600g of end-capping agent adipic acid, 28.638Kg of 4,4-diaminodicyclohexylmethane, and 31.362Kg of dodecanedioic acid were added, and the temperature was raised to 260°C and kept for 3 hours; then the system was depressurized to normal pressure, and after being evacuated to -10KPa at 250°C, the reaction system was kept for 2 hours; after continuing to evacuate to -25KPaG, the reaction system was kept for 2 hours; evacuated to -50KPaG and kept for 1 hour, after the system returned to normal pressure, the material was discharged at 250°C and water-cooled and pelletized to obtain nylon resin.
[0054] Example 1
[0055] In a 1m 3 In a stirring container, 254.4 kg of laurolactam, 20 kg of water, 600 kg of end-capping agent adipic acid, 21.479 kg of 4,4-diaminodicyclohexylmethane, and 23.521 kg of dodecanedioic acid were added, and the temperature was raised to 260 ° C and kept for 3 hours; then the system was depressurized to normal pressure, and the reaction system was kept at 250 ° C, 20 KPaG for 1 hour; evacuated to -80 KPaG and kept for 1 hour, and after the system returned to normal pressure, the material was discharged at 250 ° C and water-cooled and pelletized to obtain nylon resin.
[0056] Example 2
[0057] In a 1m 3 In a stirring container, 239.4 kg of lauryl lactam, 20 kg of water, 600 kg of end-capping agent adipic acid, 28.638 kg of 4,4-diaminodicyclohexylmethane, and 31.362 kg of dodecanedioic acid were added, and the temperature was raised to 260 ° C and kept for 3 hours; then the system was depressurized to normal pressure, and the reaction system was kept at 250 ° C, 20 KPaG for 2 hours; evacuated to -80 KPaG and kept for 1 hour, and after the system returned to normal pressure, the material was discharged at 250 ° C and water-cooled and pelletized to obtain nylon resin.
[0058] Example 3
[0059] In a 1m 3 In a stirring container, 224.4 kg of lauryl lactam, 20 kg of water, 600 kg of end-capping agent adipic acid, 35.798 kg of 4,4-diaminodicyclohexylmethane, and 39.202 kg of dodecanedioic acid were added, and the temperature was raised to 260 ° C and kept for 3 hours; then the system was depressurized to normal pressure, and the reaction system was kept at 250 ° C, 10 KPaG for 3 hours; evacuated to -70 KPaG and kept for 1.5 hours, and after the system returned to normal pressure, the material was discharged at 250 ° C and water-cooled and pelletized to obtain nylon resin.
[0060] Example 4
[0061] In a 1m 3In a stirring container, 239.4Kg of laurolactam, 20Kg of water, 600g of end-capping agent adipic acid, 30.519Kg of 3,3-dimethyl-4,4-diaminodicyclohexylmethane, and 29.481Kg of dodecanedioic acid were added, and the temperature was raised to 260°C and kept for 3 hours; then the system was depressurized to normal pressure, and the reaction system was kept at 250°C and 20KPaG for 1.5 hours; the system was evacuated to -80KPaG and kept for 1 hour. After the system returned to normal pressure, the material was discharged at 250°C and water-cooled and pelletized to obtain nylon resin.
[0062] Example 5
[0063] In a 1m 3 In a stirring container, 224.4 kg of laurolactam, 20 kg of water, 600 kg of end-capping agent adipic acid, 38.149 kg of 3,3-dimethyl-4,4-diaminodicyclohexylmethane, and 36.851 kg of dodecanedioic acid were added, and the temperature was raised to 260 ° C and kept for 3 hours; then the system was depressurized to normal pressure, and the reaction system was kept at 250 ° C, 30 KPaG for 2 hours; evacuated to -80 KPaG and kept for 1 hour, and after the system returned to normal pressure, the material was discharged at 250 ° C and water-cooled and pelletized to obtain nylon resin.
[0064] Example 6
[0065] In a 1m 3 In a stirring container, 254.4Kg of lauryl lactam, 20Kg of water, 600g of end-capping agent adipic acid, 25.14Kg of 4,4-diaminodicyclohexylmethane, and 19.86Kg of isophthalic acid were added, and the temperature was raised to 260°C and kept for 3 hours; then the system was depressurized to normal pressure, and the reaction system was kept at 250°C and 10KPaG for 2 hours; the system was evacuated to -80KPaG and kept for 1 hour. After the system returned to normal pressure, the material was discharged at 250°C and water-cooled and pelletized to obtain nylon resin.
[0066] Example 7
[0067] In a 1m 3 In a stirring container, 254.4 kg of lauryl lactam, 20 kg of water, 600 kg of end-capping agent adipic acid, 26.52 kg of 3,3-dimethyl-4,4-diaminodicyclohexylmethane, and 18.48 kg of isophthalic acid were added, and the temperature was raised to 260 ° C and kept for 3 hours; then the system was depressurized to normal pressure, and the reaction system was kept at 250 ° C, 20 KPaG for 2 hours; evacuated to -90 KPaG and kept for 1 hour, and after the system returned to normal pressure, the material was discharged at 250 ° C and water-cooled and pelletized to obtain nylon resin.
[0068] Example 8
[0069] In a 1m 3In a stirring container, 224.4Kg of laurolactam, 20Kg of water, 600g of end-capping agent adipic acid, 28.877Kg of 1,4-cyclohexanediamine, and 46.123Kg of dodecanediolacid were added, and the temperature was raised to 260°C and kept for 3h; then the system was depressurized to normal pressure, and the reaction system was kept at 250°C, 30KPaG for 3h; the system was evacuated to -80KPaG and kept for 1h. After the system returned to normal pressure, the material was discharged at 250°C and water-cooled and pelletized to obtain nylon resin.
[0070] Example 9
[0071] In a 1m 3 In a stirring container, 254.4Kg of lauryl lactam, 20Kg of water, 600g of end-capping agent adipic acid, 34.849Kg of 1,4-cyclohexanediamine, and 40.151Kg of isophthalic acid were added, and the temperature was raised to 260°C and kept for 3 hours; then the system was depressurized to normal pressure, and the reaction system was kept at 250°C, 30KPaG for 2 hours; the system was evacuated to -90KPaG and kept for 1 hour. After the system returned to normal pressure, the material was discharged at 250°C and water-cooled and pelletized to obtain nylon resin.
[0072] Test Case
[0073] The nylon resins obtained in Comparative Examples 1-2 and Examples 1-9 were tested for relative viscosity, molecular weight distribution, temperature and heat release of cold crystallization exothermic peak, color uptake and color fastness after dyeing.
[0074] Table 1 Comparative Examples 1-2 and Examples 1-9 Nylon Resin Test Results
[0075]
[0076]
[0077] Those skilled in the art will appreciate that, based on the teachings of this specification, some modifications or adjustments may be made to the present invention, and these modifications or adjustments should also be within the scope defined by the claims of the present invention.
Claims
1. A nylon resin, characterized in that: The DSC curve of the nylon resin is tested using a rapid scanning calorimeter. The temperature is first increased to 220°C at a rate of 10K / min, then decreased to 20°C at a rate of 30K / min, and then increased to 220°C at a rate of 10K / min. During the second heating process, a cold crystallization exothermic peak is generated. The cold crystallization exothermic peak temperature is 75-95°C, preferably 90-95°C, and the cold crystallization heat release is 55-75J / g, preferably 70-75J / g.
2. The nylon resin according to claim 1, characterized in that The relative viscosity measured in m-cresol solvent at 25°C and 0.5 g / dL concentration was 2.0-2.
2.
3. The nylon resin according to claim 1 or 2, characterized in that: The molecular weight distribution of the nylon resin was measured by gel permeation chromatography in hexafluoroisopropanol solvent and was found to be 2.85-3.
15.
4. The method for preparing nylon resin according to any one of claims 1 to 3, characterized in that: The method comprises the following steps: mixing diamine, dicarboxylic acid, lactam, water, an optional catalyst and an optional end-capping agent, and controlling the pressure, temperature and time of the reaction process to perform polymerization reaction to obtain nylon resin.
5. The preparation method according to claim 4, characterized in that: The following steps are included: (1) mixing lactam, diamine, dicarboxylic acid, water and end-capping agent and reacting them, and then releasing the pressure of the reaction system to normal pressure; (2) The reaction temperature is controlled at 240-260°C, and the reaction system is kept at 10-30 KPaG for 1-3 hours; (3) The reaction temperature is controlled at 240-260°C, and the reaction system is evacuated at a pressure of -70 to -90 KPaG for 0.5 to 1.5 h; (4) The reaction system is restored to normal pressure, and the discharged material is water-cooled and pelletized to obtain nylon resin.
6. The preparation method according to claim 5, characterized in that: In step (1), the reaction temperature is 240-280° C. and the reaction residence time is 3-5 h.
7. The preparation method according to any one of claims 4 to 6, characterized in that: The diamine is an alicyclic diamine, preferably one or more of 4,4-diaminodicyclohexylmethane, 3,3-dimethyl-4,4-diaminodicyclohexylmethane, 4,4-isopropyldicyclohexylamine, 2,4-methylcyclohexanediamine, 1,4-cyclohexanediamine, 1,3-cyclohexanedimethylamine, isophoronediamine, and 1,2-cyclohexanediamine.
8. The preparation method according to any one of claims 4 to 6, characterized in that: The dicarboxylic acid is selected from one or more of isophthalic acid, terephthalic acid, undecanedioic acid, dodecanedioic acid, tridecanedioic acid, and tetradecanedioic acid.
9. The preparation method according to any one of claims 4 to 6, characterized in that: The lactam is selected from laurolactam and / or caprolactam; and / or: the end-capping agent is selected from one or more of oxalic acid, adipic acid, sebacic acid, terephthalic acid, and isophthalic acid; and / or: the catalyst is selected from one or more of dibutyl phosphate, sodium hypophosphite, hypophosphorous acid, trimethyl phosphate or triphenyl phosphite; Preferably, the total mass fraction of the diamine and the dicarboxylic acid is 15-25% relative to the total mass of the nylon resin; Preferably, the mass fraction of lactam is 74.8-84.8% relative to the total mass of nylon resin; Preferably, the mass ratio of water to nylon resin is 1:(5-30), more preferably 1:(15-20).
10. Use of the nylon resin according to any one of claims 1 to 3 or the nylon resin prepared by the preparation method according to any one of claims 4 to 9 in the field of textile fiber dyeing.
Citation Information
Patent Citations
Copolymerized transparent nylon and synthesis method thereof
CN106832264A
Transparent nylon resin as well as preparation method and application thereof
CN115894902A
Nylon 12 resin as well as preparation method and application thereof
CN117343316A
Transparent long-chain polyamide and preparation method thereof
CN117801264A
Cited By
Nylon 12 fiber and preparation method and application thereof
CN120683624A
Copolymerized transparent polyamide and preparation method thereof
CN121736265A